The impact of the end of the Cold War on transition in South Africa - Du Preez, Roni (Rhodes University, Faculty of Humanities, Department of Political Studies, 1994)
This thesis argues that F.W. de Klerk's historic February 1990 speech was the end product of a set of circumstances in recent South African and global history which made possible the new phase of transitional politics which South Africa is currently experiencing. It seeks to establish that of all the factors that contributed to change, it was the late 1980s thaw in the Cold War, and its resultant repercussions internationally and regionally which was the catalytic factor which made the new era possible. In all the literature on transition there has been no comprehensive analysis of the plausible link between the two superpowers agreeing in the mid-1980s to abandon confrontational practices and to change their approaches to regional conflicts and the South African government agreeing to negotiate for a new political dispensation. This thesis will seek to establish and analyse such a link. By 1986 there was in certain governmental circles a non-public view that the policy of apartheid had failed both as a solution to the problem of black political aspirations and as a legitimating ideology. Constraining any serious move towards political change was a widely held fear at the top level of government that an accelerated reform process would make South Africa vulnerable to external aggression and internal revolutionary forces. This thesis suggests that the collapse of communist rule in Eastern Europe and the 'new political thinking' in Soviet foreign policy resulted in the notion of a communist-inspired total onslaught against South Africa losing currency - as did the position of those within the ruling elite who remained dogmatically attached to it. The end of the Cold War is the common thread which links South Africa's international , regional and domestic environments. Two important events occurred in the international and regional arenas, which against the backdrop of the end of the Cold War, strengthened the credibility of the alternative view in government: (i) the October 1986 Reykjavik Summit and (ii) the South African Defence Force setback at Cuito Cuanavale. P.W. Botha's resignation as leader of the National Party and soon after as State President created the political space through which the view of the reformers could emerge as dominant. Recognising that neither the international nor regional environments sustained the beliefs and fears held by the military hawks, F.W. de Klerk was able to capitalise on the ambience of negotiations and apply it to the South African situation. De Klerk's February 1990 speech was therefore the culmination of a process which had its origins in the mid-1980's.
Keywords: Cold War|International relations|South Africa -- Politics and government -- 1989-1994|South Africa -- Foreign relations -- 1989-1994|South Africa -- Politics and government -- 1978-1989|South Africa -- Foreign relations -- 1978-1989